Improving Learning Activities Using Tourism Awareness Education Modules for Managers of Aceh Traditional House Cultural Tourism Objects - Eviana Sonata; Rahmi Novalita; Rambang Muharramsyah (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
This study aims to analyze the increase in learning activities using tourism awareness education modules for managers of traditional Acehnese house cultural tourism objects. This type of research uses Research & Development (R&D) research. The study population is the managers of the traditional Acehnese house cultural tourism object Teungku Chik Awe Geutah, totaling 20 people. The sampling technique used incidental sampling. Data collection techniques used observation and documentation. Data collection tools used observation sheets. Data analysis techniques used descriptive percentage analysis. The results of the study showed that there was an increase in student learning activities using the module. Learning activities in the first meeting obtained a result of 99%, the second learning activity activity obtained an average score of 96%, the third learning activity activity obtained 97%, and the fourth learning activity activity obtained a score of 97.6%. Overall, learning activities using the tourism awareness education module were classified as very good with an acquisition of 97.4%. This shows that the tourism awareness education module can increase students' knowledge in managing good cultural tourism objects.